2013
DOI: 10.1039/c3cy00267e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of synthesis methods on Cu species and active sites over Cu/SAPO-34 for NH3-SCR reaction

Abstract: The changed status of copper species and active Cu sites of NH 3 -SCR over the Cu/SAPO-34 zeolites synthesized by three different methods has been investigated in this work. The combination of the EPR, H 2 -TPR and SEM results demonstrate that different synthesis methods do not affect the types of Cu species, but affect the distribution. The dominant Cu species is CuO-clusters for the precipitation sample, and it is isolated Cu 2+ for the ion-exchange sample. While, for the one-pot catalyst, both isolated Cu 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 30 publications
(39 reference statements)
3
55
1
1
Order By: Relevance
“…5, Cu x -SAPO-34 maintained the CHA framework structure basically after high temperature calcination. However, two extra peaks at 35.29°and 38.49°related to CuO phases were observed in Cu 6.62 -SAPO-34 and Cu 8.84 -SAPO-34 [30,31]. In the Cu x -SAPO-34 with low Cu loading (<5.15 wt.%), no Cu-related phases were observed in the XRD patterns, suggesting that copper oxide was present in a highly dispersed amorphous state.…”
Section: Powder Xrdmentioning
confidence: 87%
“…5, Cu x -SAPO-34 maintained the CHA framework structure basically after high temperature calcination. However, two extra peaks at 35.29°and 38.49°related to CuO phases were observed in Cu 6.62 -SAPO-34 and Cu 8.84 -SAPO-34 [30,31]. In the Cu x -SAPO-34 with low Cu loading (<5.15 wt.%), no Cu-related phases were observed in the XRD patterns, suggesting that copper oxide was present in a highly dispersed amorphous state.…”
Section: Powder Xrdmentioning
confidence: 87%
“…Wang et al found that the diffraction peaks for ion-exchanged zeolites moved to slightly lower angles with respect to the unexchanged support, suggesting that the SAPO-34 lattice had expanded with incorporation of the Cu ions into Most diffractograms in Figure 1 are very similar to that of pure SAPO-34, indicating that the chabazite (CHA) structure was maintained during ion exchange. [20,22,23], but the diffractograms do not display any evidence of these species, presumably because the copper oxide content is relatively low and consists of isolated ions or because it is very well dispersed [22,23]. Wang et al found that the diffraction peaks for ion-exchanged zeolites moved to slightly lower angles with respect to the unexchanged support, suggesting that the SAPO-34 lattice had expanded with incorporation of the Cu ions into the pores.…”
Section: Characterisation By X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Cu2O or CuO phases may be expected at ca. 2θ = 35.29, 36.30, 38.49 and 38.72° [20,22,23], but the diffractograms do not display any evidence of these species, presumably because the copper oxide content is relatively low and consists of isolated ions or because it is very well dispersed [22,23]. Wang et al found that the diffraction peaks for ion-exchanged zeolites moved to slightly lower angles with respect to the unexchanged support, suggesting that the SAPO-34 lattice had expanded with incorporation of the Cu ions into Most diffractograms in Figure 1 are very similar to that of pure SAPO-34, indicating that the chabazite (CHA) structure was maintained during ion exchange.…”
Section: Characterisation By X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Yu et al [95] further reported that the NH 3 -SCR activity of a Cu/SAPO-34 catalyst was closely related to its acid density in the whole temperature range. It was very interesting that, different from the decreased activity observed over aged Cu-SSZ-13 catalysts, better NH 3 -SCR performance was always observed over Cu-SAPO-34 catalysts, and this difference was related to the redistribution of Cu species in Cu-SAPO-34 catalysts [96,97], which will be discussed in the following parts of this chapter. In brief, the degree of Cu exchange, the type of zeolite framework and heteroatom substitution in the framework all affect the NH 3 -SCR activity and hydrothermal stability of the final Cu-CHA catalysts, and a comprehensive understanding of these effects is helpful to enhance their deNO x performance to meet the upcoming stringent NO x emission standards for diesel engines.…”
Section: Nh 3 -Scr Performance and Hydrothermal Stability Of Cu-cha Cmentioning
confidence: 83%
“…Therefore, ion exchange is the most common method for the preparation of Cu-SSZ-13 catalysts in previous literature. Ion-exchange and precipitation methods were also used to prepare Cu-SAPO-34 catalysts, and both CuO and isolated Cu 2+ ions were formed in the final catalysts no matter which method was chosen [96,97,99,100]. The different synthesis methods did not change the types of Cu species in the final catalysts, but greatly affected their distribution [97].…”
Section: Structure-activity Relationship Of Cu-cha Catalysts In Nh 3 mentioning
confidence: 99%